1999
DOI: 10.1016/s0378-3774(99)00031-1
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of soil-water distribution under ridge and bed cultivated potatoes

Abstract: Data is presented comparing infiltration of irrigation and rain water to potato crops planted in ridges and beds in East Anglia, UK. An automatic soil water station (ASWS) was used to monitor soil water content and potential in the two cultivation systems. The ASWS data indicated that most of the water bypassed the potatoes planted in ridges as irrigation water applied to the crop from a boom irrigator was shed off the ridges infiltrating in the furrows. This was due to the water repellent nature of the sandy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
41
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 12 publications
8
41
0
Order By: Relevance
“…Three years of monitoring of soils under humid temperate pine forest and grassland revealed that SWR was present for most of the summer and autumn. The presence of SWR at these locations was consistent with previous studies that also reported severe SWR for UK grassland, forest and heath (Doerr et al, 2006), arable land (Robinson, 1999;Hallett et al, 2001) and on golf greens (York and Canaway, 2000), and in the Netherlands on grasscovered sand dunes under a similar climate (Dekker and Ritsema, 1996a;Ritsema and Dekker, 2000). Both investigated sites were under permanent vegetation, which is generally considered to be a state most susceptible to SWR development Woche et al, 2005) due to the continuous input of hydrophobic substances from the vegetation and soil microbes , and a low level of soil disturbance.…”
Section: Temporal Variations In Swrsupporting
confidence: 91%
“…Three years of monitoring of soils under humid temperate pine forest and grassland revealed that SWR was present for most of the summer and autumn. The presence of SWR at these locations was consistent with previous studies that also reported severe SWR for UK grassland, forest and heath (Doerr et al, 2006), arable land (Robinson, 1999;Hallett et al, 2001) and on golf greens (York and Canaway, 2000), and in the Netherlands on grasscovered sand dunes under a similar climate (Dekker and Ritsema, 1996a;Ritsema and Dekker, 2000). Both investigated sites were under permanent vegetation, which is generally considered to be a state most susceptible to SWR development Woche et al, 2005) due to the continuous input of hydrophobic substances from the vegetation and soil microbes , and a low level of soil disturbance.…”
Section: Temporal Variations In Swrsupporting
confidence: 91%
“…With both methods, measurements were carried out ∼ 0.5 m from the ESU diagonal at a SSP in the middle of neighboring planting rows. A high small-scale soil moisture variability is to be expected on potato fields with high values on the furrow bottom and low values on the furrow ridge (Robinson, 1999). Thus, five measurements were performed per examined SSP: one in the middle of the furrow ridge centered between neighboring plants and two additional measurements on each side, i.e., one measurement in the middle of the slope and another one at the bottom of the furrow, respectively.…”
Section: Soil Moisturementioning
confidence: 99%
“…The traditional ridged-row planting configuration is no longer necessary for irrigation water distribution and may actually be antagonistic to efficient water management under high application rate (center pivot) sprinkler irrigation. Runoff from the sides of the ridged potato row leads to water ponding in the furrow and water infiltration below and to the side of a substantial percentage of the potato root zone (Saffigna et al 1976;Curwen and Massie 1984;Robinson 1999;Essah and Honeycutt 2004) resulting in sub-optimal water application efficiency and nitrogen (N) leaching (Saffigna et al 1976).…”
Section: Introductionmentioning
confidence: 99%